Avaliação da potencial aplicação de derivados de 2-acetilpiridina N-4 fenil tiossemicarbazonas em terapia e diagnóstico oncológico - Marcella Araugio Soares (2013)
Despite the wide range of antineoplastic agents available, resistance of some types of cancer and toxicity to normal cells have been identified as the main causes of treatment failure and death. The lack of early and precise diagnosis is also responsible for reducing survival of cancer patients. In this context, the development of substances with low toxicity and therapeutic potential and/or diagnosis purpose, is the major tool in an attempt to increase the survival of patients and assure the safety and efficacy of treatment. Thiosemicarbazones (TSC) are a class of synthetic compounds that have several biological activities, including antitumor. Although several studies have shown the great potential of TSC as therapeutic and / or diagnostic agents, different chemical modifications performed on this class of molecules indicate new possibilities for applications and still require further studies. The objective of this study was to evaluate the potential applicability of 2-acetylpyridine N-4-phenyl thiosemicarbazones derivatives for cancer therapy and diagnosis. The results showed that all 13 TSC tested were cytotoxic to breast and glioblastoma tumor cell lines, presenting higher in vitro antitumor activity than etoposide, an antineoplastic and inhibitor of topoisomerase II frequently used for cancer therapy. The TSC that have halogen or nitro on ortho position showed higher antitumor activity in vitro than their isomers with halogen or nitro on meta or para position of the phenyl group. H2Ac4oFPh and H2Ac4oClPh compounds showed the highest antitumor activity among all tested compounds, with IC50 in nanomolar order. These TSC induced cell death by apoptosis and oxidative stress was responsible, at least in part, for this type of cell death. The 5 mg.kg-1 H2Ac4oFPh dose, administered s.c., for 4 consecutive days, did not induce important toxicity; however, the same treatment protocol was not effective for tumor growth reduction in an animal model of brain tumor. Radioactive probes of H2Ac4oFPh were synthesized using 111In or 67Ga as radiotracers, with satisfactory specific activity and radiochemical purity. H2Ac4oFPh-111In was more useful than H2Ac4oFPh-67Ga, with higher specific activity, better chemical purity, better in vitro stability, higher distribution volume, faster blood clearance and, therefore, was considered the most promising for application in molecular imaging studies. H2Ac4oFPh-111In also showed high lipophilicity and was internalized by glioblastoma cells in vitro. H2Ac4oFPh-111In showed significative tumor uptake in vivo, however, the high abdominal uptake and high background did not allow a good visualization of tumor in imaging studies. Unlike intravenous administration, intratumoral administration allowed greater diffusion and retention of H2Ac4oFPh-111 In in the tumor site and significantly reduced the activity accumulated in the organs. These results encourage new experiments to be performed in order to promote the complexation of H2Ac4oFPh with particle emitters, such as ytrium-90, to evaluate its application in local radioisotopic therapy for glioblastoma multiforme.